Alexander of Aphrodisias and his Doctrine of the soul : 1400 years of lasting significance - Kessler, Eckhard (Brill, 2011)
This book describes the doctrine and impact of Alexander of Aphrodisias, the second-century commentator on Aristotle, through the centuries and up to his sixteenth-century role as the clandestine prompter of a new philosophy of nature. In the millennium after his death, Alexander first served the Neo-Platonic schools as their authority on Aristotle, and in the Arabic centuries subsequently served as Averroes¿́¿ exemplary exponent of the doctrine of the mortality of the soul. For this reason, the Latin Scholastics deemed his work unworthy of being translated. This changed only in the late Middle Ages, when Alexander emerged as the only Aristotelian alternative to Averroes. When in 1495 his account of Aristotle¿́¿s psychology was translated and published, his principles of a natural philosophy, which were exempt from metaphysics and based on sense perception, eventually became accessible. The prompt reception and widespread endorsement of Alexander¿́¿s teaching testify to his impact throughout the sixteenth century. Originally published as Volume XVI, No. 1 (2011) of Brill's journal Early Science and Medicine.